English Teachers’ Emotions and Regulation Strategies in Response to Students’ Disruptive Behaviour - Thinley Wangdi; Karma Sonam Rigdel (Profile: Issues in Teachers' Professional Development)
This study explored the emotions and coping strategies of 25 Bhutanese English teachers in response to student disruption. Thematic analysis of in-depth interviews revealed that the participants encountered a variety of students’ disruptive behaviours that elicited a wide range of emotions, both positive (e.g., compassion and pride) and negative (e.g., frustration, irritation, anger, sadness, anxiety, insult, guilt, and disappointment). Findings also indicated that teachers regulate their emotions using both antecedent-focused (e.g., situation selection, situation modification, attention deployment, and cognitive change) and response-focused (e.g., emotion suppression, deep breathing, journaling, talking with colleagues or students, listening to music, and watching movies) emotion regulation strategies. The study concludes with practical implications for policymakers, teachers, and teacher educators and recommendations for future research.